Teacher's Choice of Organizational Forms of Learning in a Virtual Educational Environment as a Pedagogical Problem - S.V. Mamadzhanova (Zien Journals, 2022)
The educational environment today is rapidly changing due to new realities and new learning needs. One of the currently most demanded areas of innovation is the organization of new forms of education in a virtual educational environment. The article discusses the role of a teacher in a virtual educational environment, new functions that a modern teacher should take on, which requires new knowledge and competencies from him.
Keywords: virtual educational environment; teacher's virtual environment; form of education